Socio-Cultural and Cognitive Variables and Reading Literacy Acquisition in Lima, Peru (Revista Peruana de Investigación Educativa, 2011)
This research is composed of three studies where students and teachers from two social economic groups in Lima participated. Reading literacy was measured using an adaptation of the PIRLS Reading Literacy test. Structural Equation Modelling and ANOVA were used to analyze data. Study 1 examined to what extent the variation in reading literacy in fourth grade children can be predicted from their reading motivation, strategy, vocabulary, and word decoding, and from background variables: intellectual maturity, gender, home literacy climate, and social economic status. Study 2 investigated to what extent the performance of students on reading literacy, word decoding, vocabulary and reading motivation at the end of the fifth grade can be explained from the same group of variables measured at the beginning of the fifth grade and from the background variables. Study 3 examined if the development of reading literacy and reading motivation of 202 fifth graders can be improved by means of an engaged reading programme. Results of all three studies showed that the strongest variables that contribute to reading literacy development in students are vocabulary, word decoding, reading motivation and social economic status which is related with home literacy climate. A second group of contributors to reading literacy development consists of gender and intellectual maturity, which might be important more in older than in younger children. The results evidences the importance of an engagement perspective and a cultural diversity approach while designing intervention programmes on reading literacy development.
Keywords: reading; vocabularies; motivation; social status; primary teacher education